Are migrants in large cities underpaid? Evidence from Vietnam - Cuong Viet Nguyen; Thai Pham Minh (IZA Journal of Migration, 2016)
This paper examines the wage gap between migrants and non-migrants in large cities in Vietnam. It finds that migrants receive substantially lower wages than non-migrants. The wage gap tends to be larger for older migrants. However, once observed demographic characteristics of workers are controlled, there are no differences in wages between migrants and non-migrants. The main difference in observed wages between migrants and non-migrants is explained by differences in age and education between migrants and non-migrants.
Keywords: O15; R23; I32; 330; Migration; Underpaid wages; Decomposition; Household survey; Vietnam